The acoustic repertoire of lycaenid butterfly larvae. Issue 1 (2nd January 2017) - Riva, Federico; Barbero, Francesca; Bonelli, Simona; Balletto, Emilio; Casacci, Luca P.
Abstract: Sounds and vibrations play vital roles in intra- and inter-specific communication of many insect taxa, for sexual display, defence and social recruitment. In Lepidoptera, sound production occurs in larvae, pupae and adults and has evolved in response to selection of sexual or defensive traits. About 75% of the 6000 estimated lycaenid butterflies are associated with ants (termed "myrmecophilous species") and many species produce acoustic emissions during pre-imaginal development. It was initially believed that these acoustic emissions were only produced by myrmecophilous species, but later studies showed that the ability to produce sounds may be universal among this butterfly family. The acoustic repertoire of the late-instar larvae of 12 lycaenid species (Polyommatinae and Lycaeninae), showing different degrees of interaction with ants, was analysed by investigating 12 acoustic parameters measured on the call fundamental unit (pulse). All samples produced species-specific calls whose spectra were characterized by harmonic frequency components. The inter-specific call diversity better reflects the level of association with ants than the taxonomic relationships between species. Our results support the hypothesis that the ability to emit acoustic signals is widespread in lycaenids, and that these emissions play a role in myrmecophilous interactions.